2017
DOI: 10.1080/10942912.2017.1375514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the taste-active and volatile compounds in stewed meat from the Chinese yellow-feather chicken breed

Abstract: Effects of stewing time (1, 2, and 3 h) on the levels of taste-active and volatile compounds were measured. The flavor characteristics of the stewed yellow-feather chicken meat were assessed with sensory evaluation and electronic nose. Results showed that increasing stewing time significantly decreased the contents of taste components such as free amino acids, 5′-nucleotides, minerals. Inosine 5′-monophosphate and chloride were the major umami-related compounds in stewed meat and decreased significantly during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 45 publications
8
57
2
1
Order By: Relevance
“…The results showed that spices addition could increase the content of flavor substances in stewed beef broth. Qi et al () determined and calculated that the EUC value of Chinese yellow‐feather chicken was 8.50 g MSG/100 g, which was higher than the EUC value (3.50 g MSG/100 g) of stewed beef broth (s‐b‐b) in this work. The EUC values of the s‐b‐o and s‐b‐o‐o were 42.45 and 45.48 g MSG/100 g, respectively, which was significantly higher than the s‐b‐b and s‐b‐b‐s.…”
Section: Resultscontrasting
confidence: 52%
See 4 more Smart Citations
“…The results showed that spices addition could increase the content of flavor substances in stewed beef broth. Qi et al () determined and calculated that the EUC value of Chinese yellow‐feather chicken was 8.50 g MSG/100 g, which was higher than the EUC value (3.50 g MSG/100 g) of stewed beef broth (s‐b‐b) in this work. The EUC values of the s‐b‐o and s‐b‐o‐o were 42.45 and 45.48 g MSG/100 g, respectively, which was significantly higher than the s‐b‐b and s‐b‐b‐s.…”
Section: Resultscontrasting
confidence: 52%
“…However, the contents of total bitter taste free amino acids in raw beef were higher, such as the content of Arg in raw beef, which was the highest in all 6 samples with different stewing time. Qi et al () determined the taste‐active compounds in stewed Chinese yellow‐feather chicken soup. The content of total free amino acids was 258.52 μg/g in the raw chicken meat, and stewing significantly reduced the concentration of free amino acids in chicken meat.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations